Determination of Boric Acid Levels in Food Samples Using the UV-Vis Spectrophotometry Method - Anjelli Putri Gunawan; Alidya Fitri Kusuma Wardani; Ria Hikmarina; Rahmi Rahmi; Madyawati Latief (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2022)
Food is a basic need for every human being to grow and maintain life. In food there is what is called BTP or Food Additives. According to the Regulation of the Minister of Health of the Republic of Indonesia No. 033 of 2012 concerning food additives , boric acid or borax is one of the types of food additives that are prohibited from being used in food products. However, in reality many people still use boric acid as BTP in producing food. The purpose of this study was to identify and determine boric acid levels in food samples. Quantititative analysis was performed using the liquid curcumamine addition method, while quantitative analysis used the UV-Vis spectrophotometry method at a maximum wavelength of 540 nm. The results of the identification and determination of boric acid levels showed that sample A had a color change from purplish red to brick red which indicated that the food sample was positive for containing boric acid. The average level of boric acid in sample A was 986.947 ppm. The %RSD value obtained is 1.583% which indicates that this test has good precision.